1983
DOI: 10.4315/0362-028x-46.7.610
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Microbial Growth on Modified Atmosphere-Packaged Fish

Abstract: Four species of fish from Atlantic waters, Meronia americanus (perch), Cynoscion regalis (seatrout), Micropogon undulatis (croaker) and Pomatomus saltatrix (bluefish), were processed (gutted or filleted), packaged under carbon dioxide and refrigerated. Stability of the fish under the modified atmosphere preservation (MAP) system was compared to that of fish stored conventionally. Use of the MAP system resulted in a 45 to 55% increase in stability, primarily due to an extension in the lag phase of psychrotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Modified atmosphere packaging (MAP) has been reported to increase shelf-life of muscle foods (Gray et al, 1983;Brody, 1989). Carbon dioxide selectively inhibited psychrotrophic, aerobic, and gram-negative bacteria (Lannelongue et al, 1982;Stenstrom, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Modified atmosphere packaging (MAP) has been reported to increase shelf-life of muscle foods (Gray et al, 1983;Brody, 1989). Carbon dioxide selectively inhibited psychrotrophic, aerobic, and gram-negative bacteria (Lannelongue et al, 1982;Stenstrom, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Woyewoda et al (6) concluded that the increase in shelf-life of cod was too minimal when compared to the increased costs of modified atmosphere packaging (MAP). Very high CO 2 concentrations cannot be used in fish packaging because of the development of excessive drip, and metallic and sour off-odours and off-flavours (7,8). On the other hand, according to Randell et al (8) and Cann et al (9,10), drip in fish packed in 40-60% CO 2 was smaller than or equal to vacuum-packed fish.…”
Section: Introductionmentioning
confidence: 99%
“…Gas packaging is an effective way to increase the shelf-life of many products. In many studies, gas packaging has increased the shelf-life of fish when compared to over-wrap packaging (2,3) or vacuum-skin packaging (4). However, gas packaging cannot be used for all fish species.…”
Section: Introductionmentioning
confidence: 99%
“…enteritidis and stored in various atmospheres (under for Salmonella spp. have been reported for fish (Gray et al 1983), poultry (Gray et al 1984) andbeef (Nychas et al 1993). Indeed Nychas et al (1993) reported that a O"C, under vacuum, 50% C02/50% N2 and 100°/o CO, atmospheres, Salm.…”
Section: Nd Not Determinedmentioning
confidence: 89%